Affective Eye Contact: An Integrative Review - Hietanen, Jari K. (Frontiers in Psychology, 2018)
In recent years, many studies have shown that perceiving other individuals’ direct gaze has robust effects on various attentional and cognitive processes. However, considerably less attention has been devoted to investigating the affective effects triggered by eye contact. This article reviews research concerning the effects of others’ gaze direction on observers’ affective responses. The review focuses on studies in which affective reactions have been investigated in well-controlled laboratory experiments, and in which contextual factors possibly influencing perceivers’ affects have been controlled. Two important themes emerged from this review. First, explicit affective evaluations of seeing another’s direct versus averted gaze have resulted in rather inconsistent findings; some studies report more positive subjective feelings to direct compared to averted gaze, whereas others report the opposite pattern. These contradictory findings may be related, for example, to differences between studies in terms of the capability of direct-gaze stimuli to elicit feelings of self-involvement. Second, studies relying on various implicit measures have reported more consistent results; they indicate that direct gaze increases affective arousal, and more importantly, that eye contact automatically evokes a positively valenced affective reaction. Based on the review, possible psychological mechanisms for the positive affective reactions elicited by eye contact are described.